Digital marketing: implementation of digital advertising preference to support brand awareness - Alamsyah, Doni Purnama; Indriana; Ratnapuri, Chyntia Ika; Aryanto, Rudy; Othman, Norfaridatul Akmaliah (Allied Business Academies, 2021)
Management information system is important to be part of company operation. Its implementation through digital marketing in marketing side. Based on digital marketing issue, so this study aims to examine the position of digital advertising preference as the implementation of digital marketing on company. The study is conducted by analyzing consumer needs and consumer brand awareness. It is conducted by survey to 205 consumers who have experience in accepting of digital advertising. Path analysis is conducted by using SmartPLS to examine the research hypothesis. The research findings are stated that digital advertising preference can be influenced by consumer needs. Furthermore, the implementation of digital advertising preference has positive impact to consumer brand awareness. Information of research findings is useful for company, before the implementation of digital marketing reviews the position of digital advertising preference that can stimulate of consumer brand awareness.